(untitled) (Journal of Engineering, 2010)
The science of architectural history is considered one of the basic fields of the architectural studies because it reflects civilization, intelligence and creation .The present research problem takes to account the confusion image of the importance of studying architectural history in Islamic architectural theory . Research hypothesis is ’’ The holly quran encourage research history’’. The research contain Ayat al quran that in sure the importance of studying history and explain examples from historical buildings the research in sure the importance of studying historical civilization and buildings, and draw some conclusions from al quran miracles.